Estradiol deficiency is a risk factor for idiopathic benign paroxysmal positional vertigo in postmenopausal female patients. (7th May 2017) - Yang, Hualan; Gu, Huanhuan; Sun, Wenjing; Li, Yanpeng; Wu, Huijuan; Burnee, Molorerdene; Zhuang, Jianhua
Abstract : Objectives/Hypothesis: Although it is generally considered that benign paroxysmal positional vertigo (BPPV) is associated with changes in female sex hormone levels, no direct data have been reported until now. The purpose of this article was to provide direct data showing the distinct relationship between female sex hormone fluctuations and BPPV in postmenopausal female patients. Study Design: Prospective analysis in humans and basic research in animals. Methods: Blood samples were analyzed to determine the levels of estradiol, progesterone, follicle‐stimulating hormone, and luteinizing hormone in 50‐ to 80‐year‐old postmenopausal female patients newly diagnosed with idiopathic BPPV based on history compatible with BPPV and positive provocative maneuvers. Animal models of bilateral ovariectomy and female sex hormone replacement therapy were used to further confirm the relationship between BPPV and female sex hormone levels by determining the expression levels of otoconin 90, the protein suggested as essential in the dislocation of otoconia. Results: Statistically significant differences between the estradiol level of BPPV patients and the control group were found ( P < .001). Moreover, in bilateral ovariectomy in rats, 17β‐estradiol replacement reversed the decrease of otoconin 90 levels. Conclusions: Our results suggest that estradiol deficiency may be an important risk factor for idiopathic benign paroxysmal positional vertigo in postmenopausal female patients. Level of Evidence: NA. Laryngoscope, 128:948–953, 2018